The impact of effective communication in preventing the effects of parental separation - ALTAMIMI, MASHAIL (Al-Adab Journal, 2025)
The issue of parental separation is one of the life experiences that has a profound impact on children, as it may greatly affect their psychological and emotional health. In this context, the research came to study how effective communication between parents and children mitigates the negative effects that result from separation. The research aims to reveal the role of effective communication in enhancing children’s emotional adaptation and providing effective strategies that support their well-being. Initially, the research sought to analyze the relationship between the quality of communication between parents and their children after separation. The research methodology included the use of qualitative and quantitative methods to collect data, as questionnaires were distributed to a group of families who had experienced separation, and personal interviews were conducted with specialists in psychology and family psychology. Practical cases were also studied to identify effective communication strategies and their applications. The research results showed that children who experienced effective and sustained communication with both parents after separation were less likely to have psychological problems such as anxiety and depression. This type of communication has contributed to reducing levels of stress and conflict between parents, which has a positive impact on the children. In addition, the results showed that children who received emotional support and active listening from parents were better able to adapt to changes resulting from separation. The research found that there are several strategies that contribute to improving communication between parents. The most prominent of these strategies is maintaining a high level of honesty and transparency in communicating with children about life changes. It also requires a focus on actively listening to children’s feelings and needs without prejudice. It is also important to provide consistent and reliable support for children, and to maintain daily routines as much as possible. In conclusion, the research highlights the importance of effective communication as a vital tool in reducing the negative effects of parental separation on children. It shows that improving the quality of communication between parents can play a major role in enhancing children’s well-being and facilitating their ability to adapt to life changes. Based on these findings, the study recommends the need to adopt effective communication strategies as part of family support plans, and to conduct further studies to examine the effects of effective communication on other aspects of children’s lives after separation.